Uric acid and risk factors associated with metabolic syndrome in adult population from Junin city - Carranza, Amelia E. (2011)
The objective of this study was to determine the association between serum uric acid (UA) and risk factors associated with metabolic syndrome (MS) in a high altitude population. We included 174 adults, natives from Junin city, 4107 msnm (75 men and 99 women). The prevalence of risk factors like as obesity, hypertension, hyperglycemia, hypertriglyceridemia and low serum level of HDL-cholesterol and uric acid serum level, were estimated. Subjects were stratified by gender into quartiles of serum uric acid levels. A higher prevalence of hyperuricemia in men than in women was found. It is observed that the prevalence of metabolic syndrome (MS) increases in both men and women according to quartile of serum uric acid (UA). A significant association between uric acid level and triglyceride level in both men and women was found. It is concluded that the estimated values would show the prevalence of MS in people at high altitude to be associated with serum UA level, thus seeming to be a new risk factor associated with the SM in these populations.